THE IMPACTS OF CULTIVATING INDONESIAN EFL LEARNERS’ POSITIVE SELF-ESTEEM IN SPEAKING ACTIVITIES - Kristian Florensio Wijaya (Widya Mandala Surabaya Catholic University, 2023)
ABSTRACTWith the accompaniment of positive self-esteem, EFL learners are capable of improving their speaking learning skills to the fullest development and becoming more appreciative of their existing communicative competencies. This present small-scale library study set out to profoundly explore the impacts of cultivating Indonesian EFL learners’ self-esteem in speaking activities. To comply with this study's objectivity, the researcher thematically analyzed the previously-generated research results generated by 30 self-esteem and speaking studies. The in-depth thematic analysis revealed that positive self-esteem can transfigure Indonesian EFL learners into more confident L2 speakers and lead them to obtain more satisfying speaking learning achievements. Thus, this qualitative study affirmed that in the light of positive self-esteem, Indonesian EFL learners can become more proficient L2 speakers as they have been more comfortable with themselves and the specific communicative abilities they are currently possessing.